2008
DOI: 10.1007/s11033-008-9320-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and identification of markers for toxic and non-toxic varieties of Jatropha curcas L. using RAPD, AFLP and SSR markers

Abstract: Jatropha curcas L., a multipurpose shrub has acquired significant economic importance for its seed oil which can be converted to biodiesel, is emerging as an alternative to petro-diesel. The deoiled seed cake remains after oil extraction is toxic and cannot be used as a feed despite having best nutritional contents. No quantitative and qualitative differences were observed between toxic and non-toxic varieties of J. curcas except for phorbol esters content. Development of molecular marker will enable to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
47
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 16 publications
10
47
2
5
Order By: Relevance
“…So far, several accessions of the plant are available, but still little data concerning genetic variability of Jatropha has been reported (Martínez-Herrera et al 2006, Pamidimarri et al 2008a. rDNAs of plants are genes coding for various ribosomal RNAs, including 5S and 45S rRNAs.…”
Section: Physical Mapping Of 45s and 5s Rdnasmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, several accessions of the plant are available, but still little data concerning genetic variability of Jatropha has been reported (Martínez-Herrera et al 2006, Pamidimarri et al 2008a. rDNAs of plants are genes coding for various ribosomal RNAs, including 5S and 45S rRNAs.…”
Section: Physical Mapping Of 45s and 5s Rdnasmentioning
confidence: 99%
“…So far a few molecular characterizations of J. curcas, using RAPD, AFLP, SSR markers and phylogenetic analysis based on ITS sequence of rDNA, have been reported (Pamidimarri et al 2008a, b). However the genomic distribution of rDNA loci of Jatropha species has not been studied.…”
mentioning
confidence: 99%
“…Several studies on genetic variability in Jatropha populations were reported using different molecular markers, e.g., amplified fragment length polymorphism, randomly amplified polymorphic DNA (RAPD), single primer amplification reaction, inter-simple sequence repeat (ISSR), and simple sequence repeat (SSR) [1,4,5,15,23,27,37]. DNA marker (RAPD, ISSR, and SSR) analyses revealed that the Jatropha seeds commercialized worldwide consisted of few genetically identical or closely related clones and showed very low genetic variation either within or between varieties [1].…”
Section: Introductionmentioning
confidence: 99%
“…Narrow genetic bases were reported among germplasms collected in India [4] and in China [37]. Wider variability was present among genotypes collected from different geographic areas [5] and between toxic and non-toxic genotypes collected in Mexico [23]. Recently, Ovando-Medina et al [22] summarized the genetic diversity research on Jatropha as published in indexed journals.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers were used in some studies with J. curcas, such as Random Amplification of Polymorphic DNA (RAPD) and Inter Simple Sequence Repeat (ISSR), to analyze 42 Jatropha accessions from different regions of India (Basha and Sujatha 2007) and more recently, Amplified Fragment Length Polymorphism (AFLP) and Simple Sequence Repeats (SSR), to differentiate toxic from non-toxic varieties (Pamidimarri et al 2008a). Phylogenetic studies were also performed by RAPD and AFLP for seven species of the genus (Pamidimarri et al 2008b).…”
Section: Introductionmentioning
confidence: 99%